Taboo in the Frame of Tri Hita Karana: Balinese Language Spoken in Menyali Village - Mulana, I Gusti Ketut Diksa; Mahendrayana, Gede (STKIP Agama Hindu Singaraja, 2024)
Taboo language is a local culture that is very important as the identity of each region. However, due to developments over time, culture in the form of taboo language is starting to be abandoned by Balinese people. This also happened in Menyali Village. New studies related to taboo language are urgently needed as a step to revitalize taboo language. Therefore, this research discusses taboo in Balinese language spoken in Menyali Village as a concrete action to protect taboo languages from extinction. This study focused on taboo words used in the Village of Menyali as a research object. The data was analyzed with descriptive qualitative design. Data collection was carried out through in-depth interviews with three informants and used interview guide as an instrument. The results showed that there were 45 (forty-five) taboo words used in Menyali Village. These taboo words were classified into three scopes based on the Tri Hita Karana concept, namely there were 15 words in Parhyangan, 24 words in Pawongan. and 6 words in Palemahan. This study is expected to provide implications in linguistics, especially for preserving Balinese culture in the form of taboo language.